A new type of membrane contact in the ER-Golgi system regulates autophagosome biogenesis. Issue 12 (2nd December 2021) - Li, Shulin; Zhang, Min; Ge, Liang
ABSTRACT: Formation of the double-membrane autophagosome requires membrane reorganization of the endomembrane system to generate membrane precursors. The ER-Golgi trafficking system has been shown to provide membranes for phagophore growth. Nonetheless, how the components of the ER-Golgi system are redirected toward autophagosome biogenesis remains unclear. Here, we identify a new type of membrane contact formed between the ER-Golgi intermediate compartment (ERGIC) and the ER-exit sites (ERES) under macroautophagy/autophagy-induction conditions. The ERGIC-ERES contact is established by the TMED9-PREB/SEC12 interaction and regulates the biogenesis of the ERGIC-COPII vesicles, which we found previously act as a membrane template for LC3 lipidation and autophagosome formation.